Scaphosepalum tarantula (Orchidaceae: Pleurothallidinae), a new species from Ecuador - Baquero, Luis E.; Hirtz, Alexander; Iturralde, Gabriel (Lankesteriana: International Journal on Orchidology, 2018)
A new species, Scaphosepalum tarantula, is described. It is recognized by the medium-sized plants with grey-green leaves suffused with red-brown to purple stains at the petioles; densely fimbriated, red-brown to sanguine flowers, spiky tails of the lateral sepals and a dark sanguine, wingless lip. It is here compared to Scaphosepalum fimbriatum with which it shares similarities.